PWE-113 Comparing barium swallow with high resolution manometry in the diagnosis of primary oesophageal dysmotility – a retrospective study in a tertiary centre. (17th June 2017) - Dhillon, AS; Ibraheim, H; Zeki, S
Abstract : Introduction: The gold standard for diagnosis of primary oesophageal dysmotility (POD) is high-resolution manometry (HRM). Barium swallow (BS) studies remain integral to many diagnostic algorithms for dysphagia. Our aim was to assess the sensitivity and specificity of BS in the diagnosis of POD including achalasia as defined using HRM. Method: Patients that had a BS and HRM within a year of each other over a period of 10 years were identified. Those with a history of upper gastrointestinal surgery were excluded. The HRM diagnosis was algorithmically deduced from the raw dataset using the appropriate Chicago classification 1 . All HRM diagnoses and barium term extractions were manually verified by the authors. Sensitivity, specificity, negative predictive value (NPV) and positive predictive value (PPV) and accuracy for BS were calculated for each of the positive BS terms identified. Subset analysis for achalasia specifically and all spasticity excluding achalaisa were performed. Results: Conclusion: This study suggests that BO patients with LGD have a high risk of developing HGD or Cancer. Furthermore, BO patients with ID have a low risk of progression. It is of paramount importance that patients diagnosed with LGD are intensively monitored through endoscopic surveillance or treated. ID patients should also be followed up but less frequently. This study highlighted that abnormal p53 expression detected through immunohistochemistry is a stronger predictor of malignant progression than LGD. Disclosure of Interest: None Declared